Part I. The chemistry of alpha-oxathiolane ketal radicals. Part II. The synthesis of cross-conjugated trienes using indium chemistry, their Diels-Alder reactions, and a tandem diene-transmissive and conventional Diels-Alder reaction. - Squires, Neil H. (University of Ottawa (Canada), 1998)
Part I. The $\alpha$-thionocarbonates of spiro tetrahydrofuran 42 and oxathiolanes 41 were prepared from the corresponding alcohols. Reflux in the presence of AIBN, allyltributyltin and benzene afforded no reaction with thionocarbonate 42, however under the same conditions thionocarbonate 41 formed cyclopentenyl ether 44. Barton ester 48 was prepared and photolysed in the presence of allyltributyltin at room temperature, also affording cyclopentenyl ether 44. Part II. A series of alcohols 189, obtained by the indium mediated coupling of 5-bromo-1,3-pentadiene and the corresponding aldehydes, were dehydrated with $\rm PPh\sb3/DEAD$ in benzene at $50{-}60\sp\circ\rm C.$ The novel 3-methylene substituted cross-conjugated triene 165 was reacted with a series of dienophiles in a diene-transmissive Diels-Alder study. The use of DMAD afforded adduct 171 as an inseparable mixture of diastereomers at a ratio of 2:1 (trans:cis) and dehydrogenated adduct 172. In the case of cyclic dienophiles (NPTAD, 1,4-benzoquinone and N-phenylmaleimide) the resulting adducts (168, 166, 167) were obtained in very high diastereoselectivities; 91:9 in the case of NPTAD, and $>$95:5 in the cases of 1,4-benzoquinone and N-phenylmaleimide, (trans:cis). A tandem diene-transmissive Diels-Alder and conventional Diels-Alder reaction was developed. (Abstract shortened by UMI.)
Keywords: Chemistry, Organic.